2013
DOI: 10.1098/rsta.2012.0187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the durability of composite tidal turbine blades

Abstract: The long-term reliability of tidal turbines is critical if these structures are to be cost effective. Optimized design requires a combination of material durability models and structural analyses. Composites are a natural choice for turbine blades, but there are few data available to predict material behaviour under coupled environmental and cycling loading. The present study addresses this problem, by introducing a multi-level framework for turbine blade qualification. At the material scale, static and cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…In another study, [10] presented interesting turbine performance and thrust curves, mainly oriented towards blade loads owing to oscillatory flows, similarly to [11] and [12]. Whilst some of those experimental results were used as a basis for numericalexperimental validation such as [13] and [14], none of them follow a standard experimental 25 protocol.…”
mentioning
confidence: 99%
“…In another study, [10] presented interesting turbine performance and thrust curves, mainly oriented towards blade loads owing to oscillatory flows, similarly to [11] and [12]. Whilst some of those experimental results were used as a basis for numericalexperimental validation such as [13] and [14], none of them follow a standard experimental 25 protocol.…”
mentioning
confidence: 99%
“…Yet some studies focused on the assessment of the coupled influence of water and stress [6-M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 9], mainly on thermosets composites [10][11][12][13][14][15]. These studies mostly underlined the acceleration of water diffusion in polymer resulting from the applied stress [16].…”
Section: Contextmentioning
confidence: 99%
“…Quality control checks, including interlaminar shear, revealed one set of samples to be of better quality, and tests indicated that the lower quality samples resulted in poorer fatigue performance compared to specimens of good quality [23]. For a composite marine propeller, random variations due to fiber misalignments, voids, laminate property uncertainties, and boundary conditions add to the uncertainty of the overall propeller response compared to homogeneous metallic propellers [24].…”
Section: Introductionmentioning
confidence: 99%